2011
DOI: 10.1530/rep-10-0401
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and biological activity of relaxin in porcine milk

Abstract: A lactocrine mechanism for delivery of maternally derived relaxin (RLX) into the neonatal circulation as a consequence of nursing was proposed for the pig. Immunoreactive RLX was detected in colostrum and in the serum of newborn pigs only if they were allowed to nurse. Milk-borne RLX concentrations are highest during early lactation (9-19 ng/ml), declining to !2 ng/ml by postnatal day 14. Whether milk-borne RLX is bioactive is unknown. Evidence that RLX concentrations in milk are higher than in maternal circul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 51 publications
1
18
0
Order By: Relevance
“…The increase in endometrial epithelial RXFP1 expression observed for lactocrine-null gilts at PND 2 also agrees with observations reported for whole uteri 48 h after colostrum deprivation from birth [40]. Because colostrum is a source of bioactive RLX [50], ingestion of RLX by nursing gilts may be acting in a negative regulatory manner to decrease RXFP1 expression [9]. Data indicating that RXFP1 expression is predominantly stromal agree with an earlier report [18] in which both RXFP1 mRNA and protein were localized primarily in this endometrial cell compartment at PND 14.…”
Section: Nursing and Uterine Gland Developmentsupporting
confidence: 89%
See 2 more Smart Citations
“…The increase in endometrial epithelial RXFP1 expression observed for lactocrine-null gilts at PND 2 also agrees with observations reported for whole uteri 48 h after colostrum deprivation from birth [40]. Because colostrum is a source of bioactive RLX [50], ingestion of RLX by nursing gilts may be acting in a negative regulatory manner to decrease RXFP1 expression [9]. Data indicating that RXFP1 expression is predominantly stromal agree with an earlier report [18] in which both RXFP1 mRNA and protein were localized primarily in this endometrial cell compartment at PND 14.…”
Section: Nursing and Uterine Gland Developmentsupporting
confidence: 89%
“…Mechanistically, these observations are consistent with data indicating that endometrial thickness was reduced and uterine gland genesis was inhibited by PND 14 in the absence of lactocrine signaling from birth. Lactocrine effects on patterns of cell proliferation suggest that mitogenic factors in colostrum are important for support of endometrial morphogenesis in the neonate [16,27,50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Colostrum (first milk) contains bioactive factors including relaxin, a prototypical MbF (Frankshun et al 2011), detected in the circulation of nursed pigs by 12 h postnatal (Yan et al 2006). Insulin-like growth factor 1 (IGF1; 7.6 kDa), another member of the insulin family of hormones, is found in porcine colostrum at high concentrations (Simmen et al 1990a, which decline within the first 24-36 h of lactation during the transition from colostrum to mature milk (Klobasa et al 1987, Nguyen et al 2001.…”
Section: Introductionmentioning
confidence: 99%
“…Purified RLX, extracted from porcine ovaries, was obtained from IBSA, Lugano, Switzerland [14]. RLX amount was assessed by an in house developed ELISA with a detection limit of 0.4ng/ml and high specificity due to a double antibody anti RLX detection strategy.…”
Section: Methodsmentioning
confidence: 99%